ОСНОВНЫЕ МОТИВЫ ПОЭТИКИ ВИКТОРА ЦОЯ - Абдиров, А.М. (SCIENCE and SOCIETY, 2025)
The article analyzes the poetics and figurative system of song lyrics by Viktor Tsoi, the leader of the Kino group and one of the cult representatives of Russian rock of the 1980s. Particular attention is paid to the lyrical subject and addressing in Tsoi's lyrics (the relationship between "I" and the inclusive "we", the specifics of addressing the addressee), the key figurative fields and chronotopes of his poetry (night and day, top and bottom, nature and city, path and time), as well as the formal strategies of rock poetics (metric and rhythmic features, strophic, refrain, composition).
Keywords: Viktor Tsoi; rock poetry; lyrical hero; poetics; figurative system; chronotope; motive; dolnik; refrain